Analisis Framing dalam Teks Editorial “Kuasa Polisi dalam KUHAP” di Media Online Tempo - Cinta Izzati Ananda Agris Hasibuan; Muhammad Rayhan Harahap; Shafna Jonanda Soefit Pane (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Tempo is an online media outlet that provides a dedicated editorial section as a platform for the newsroom to express criticism and perspectives on contemporary legal, political, and social issues. One of its editorials entitled “Police Power in the New Criminal Procedure Code” discusses the ratification of the revised Criminal Procedure Code (KUHAP) by the Indonesian House of Representatives, which was considered hasty and potentially beneficial to law enforcement institutions while posing risks to citizens’ rights. This study aims to analyze how Tempo frames the issue through its editorial text. The research employs a qualitative approach using Robert M. Entman’s framing analysis model, which consists of four elements: define problems, diagnose causes, make moral judgment, and treatment recommendation. The findings indicate that Tempo frames the revised KUHAP as a threat to the rule of law by enabling the potential abuse of power by the police. The editorial criticizes the legislative process for its lack of public participation and transparency, while also presenting moral evaluations of policies perceived as failing to protect citizens. Furthermore, Tempo recommends limiting police authority and strengthening oversight mechanisms to prevent arbitrariness and violence. Overall, the editorial functions as a form of media social control in monitoring legal policies that have broad implications for society.